Telling an Untold Story of Pedagogical Practices in Mathematics Education in Nepal: Envisioning an Empowering Pedagogy - Lamichhane, Basanta Raj; Luitel, Bal Chandra (Saptagandaki Journal, 2022)
Conventional mathematics education practice glorifies the hypothetico-deductive reasoning and accompanying reductionist and piecemeal pedagogy and pushes us into the grips of pouring and 'one-size-fits-all' approach (Freire, 1993; Luitel, 2009; Lamichhane, 2021). It is still being practiced and occupies the dominant role in our schools and universities. In this background, the objectives of this research were to explore the roles of existing pedagogy behind a formation of a transmissionist image of pedagogy, thereby envisioning empowering/ humanizing pedagogical practices. In so doing, I deployed an autoethnography research design (Bochner & Ellis, 2016) under interpretive, critical, and postmodern paradigms (Taylor, Taylor, & Luitel, 2012). Writing as a method of inquiry (Richardson & St. Pierre, 2017) has been used to generate field texts. To interpret and make meaning from the textual information, I have used Habermas's Knowledge Constitutive Interests (Habermas, 1972) and Jack Mezirow's Transformative Learning Theory (Mezirow, 1991) as theoretical referents. I have captured the pedagogical practices under three themes: -practice makes a man perfect! I am a successful teacher; he is our supporter! Please protect him! and I do not know anything! Prepare them for the exam. Likewise, a metaphor of empowering/humanizing pedagogy has been proposed as an inclusive pedagogy. Finally, I revealed that empowering/humanizing pedagogy supports connecting mathematical activities to the lifeworld of the learners. It promotes agentic aspects of the learners and helps them to become informed and conscious citizens so that they can contribute to creating an inclusive and socially just society.